MODERNISASI IRIGASI KEDUNGPUTRI DI PURWOREJO TAHUN 1871-1920 - Prabhakusuma, Dwipayana; Mufida, Hasna Okta (Historia, 2024)
The construction of Kedungputri Irrigation in Purworejo was carried out to overcome the economic and water crises in Purworejo. The Cultuurstelsel program, deforestation, and the Java War in the mid-19th century caused the crisis. As a solution, the colonial government carried out massive modernization and renovation of irrigation, both physically and institutionally. Modernization of Kedungputri Irrigation was carried out by making new weirs, water locks, and an institutional system that was previously managed by local officials into a special public works department by the Dutch East Indies government. These efforts resulted in an increase in agricultural and plantation yields in Purworejo so that the community's economic conditions became more stable and avoided water and economic crises. In addition, this irrigation also managed to become a power plant for school buildings, government, and military headquarters in Purworejo. In the field of geography, the expansion of irrigation resulted in changes in the morphology of the Purworejo region from moorland to cultivated land for both plantations and agriculture, as well as the expansion of residential land. The method used is the historical research method. The method consists of five stages, namely, topic selection, source study, source verification, interpretation and historiography. Keywords: Modernization; Irrigation; Kedungputri; Purworejo